2018
DOI: 10.1155/2018/1418609
|View full text |Cite
|
Sign up to set email alerts
|

p27-V109G Polymorphism Is Not Associated with the Risk of Prostate Cancer: A Case-Control Study of Han Chinese Men in Central China

Abstract: Objective We conducted an update meta-analysis aiming to verify the association between p27-V109G polymorphism and cancer risk, particular for prostate cancer (PCa). Then, we conducted a case-control study of Han Chinese in central China to verify the evidence-based results. Methods Relevant studies were collected from diverse databases up to March 2017. In addition, a hospital-based (H-B) case-control study enrolling 90 PCa patients and 140 healthy controls was included to verify these evidence-based findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…One case-control study demonstrated that p27 KIP1 rs2066827 polymorphism is associated with an increased risk of prostate cancer (31), whereas another study and a meta-analysis suggested that this polymorphism is associated with a reduced risk of prostate cancer (13,17). In addition, other studies have reported no association between the p27 KIP1 rs2066827 polymorphism and prostate cancer risk (30,32,33), which our results are in agreement with. Several possible causes can be proposed related to the inconsistency between our study and the other investigations, such as sample sizes and heterogeneous populations/ethnic variance.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…One case-control study demonstrated that p27 KIP1 rs2066827 polymorphism is associated with an increased risk of prostate cancer (31), whereas another study and a meta-analysis suggested that this polymorphism is associated with a reduced risk of prostate cancer (13,17). In addition, other studies have reported no association between the p27 KIP1 rs2066827 polymorphism and prostate cancer risk (30,32,33), which our results are in agreement with. Several possible causes can be proposed related to the inconsistency between our study and the other investigations, such as sample sizes and heterogeneous populations/ethnic variance.…”
Section: Discussionsupporting
confidence: 88%
“…We observed no significantly increased risk of prostate cancer for CDK2 rs2069408 and CCNE1 rs997669 mutant genotypes by all clinicopathological parameters. Furthermore, our data do not suggest that the p27 KIP1 rs2066827 polymorphism is associated with PSA level, Gleason score or pathological T stage, thus confirming the overall null association with the clinicopathological characteristics of prostate cancer, as reported previously (32,33). Interestingly, we did find that CCNE1 mRNA expression was significantly increased in carcinomas with Gleason scores higher than 7.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Nevertheless, another group failed to validate any correlation between this variant and susceptibility of PCa. 27 Previous meta-analysis showed evidence that the G allele of CDKN1B was correlated with a decreased risk of PCa under the dominant genetic model (OR = 0.60, 95% CI = 0.36-0.98, P = .04). 23 In the present analysis, continually appeared case-control studies were screened and more information about this CDKN1B polymorphism was identified.…”
Section: Discussionmentioning
confidence: 99%
“…They also observed that cells transfected with G‐allele showed a lower proliferative activity and expression level of p27 protein than cells transfected with V‐allele. Nevertheless, another group failed to validate any correlation between this variant and susceptibility of PCa . Previous meta‐analysis showed evidence that the G allele of CDKN1B was correlated with a decreased risk of PCa under the dominant genetic model (OR = 0.60, 95% CI = 0.36‐0.98, P = .04) .…”
Section: Discussionmentioning
confidence: 99%